The territorial capital of urban functional areas as a challenge for regional development policy: An outline of the concept - Kudłacz, Tadeusz; Markowski, Tadeusz (Journal of Public Governance, 2018)
Objective: In this article Urban Functional Areas (UFAs) and their essence of matter and leading qualities are considered through the prism of theoretical concepts such as transaction costs, the concept of territorial capital and the space of flows with connection to the network economy. Research Design & Methods: Each theoretical concept prompts its own group of intervention instruments in the processes of territorial development. On this basis the authors focus on explanation of the possibility of public intervention in the functioning and development of urban functional areas. Contribution / Value Added: This article has a theoretical character but formulates general basis for elaboration of integrated development policy on the level of local self-government co-operation”. Finding and recommendations: The authors show that the territorial authorities and enterprises in Urban Functional Areas should integrate their development policies around the “new quality resource” in the form of territorial capital. The territorial capital in UFAs of modern economies becomes the most important source of building long-lasting competitive advantages for businesses. JEL classification: R1, R5,O2